Multi‐resolution electron spectrometer array for future free‐electron laser experiments. (26th August 2021) - Walter, Peter; Kamalov, Andrei; Gatton, Averell; Driver, Taran; Bhogadi, Dileep; Castagna, Jean-Charles; Cheng, Xianchao; Shi, Hongliang; Obaid, Razib; Cryan, James; Helml, Wolfram; Ilchen, Markus; et al.
Abstract : The design of an angular array of electron time‐of‐flight spectrometers is reported, intended for non‐invasive spectral, temporal, and polarization characterization of single shots of high‐repetition rate, quasi‐continuous, short‐wavelength free‐electron lasers such as the LCLS II at SLAC. Abstract : The design of an angular array of electron time‐of‐flight (eToF) spectrometers is reported, intended for non‐invasive spectral, temporal, and polarization characterization of single shots of high‐repetition rate, quasi‐continuous, short‐wavelength free‐electron lasers (FELs) such as the LCLS II at SLAC. This array also enables angle‐resolved, high‐resolution eToF spectroscopy to address a variety of scientific questions on ultrafast and nonlinear light–matter interactions at FELs. The presented device is specifically designed for the time‐resolved atomic, molecular and optical science endstation (TMO) at LCLS II. In its final version, the spectrometer comprises up to 20 eToF spectrometers aligned to collect electrons from the interaction point, which is defined by the intersection of the incoming FEL radiation and a gaseous target. The full composition involves 16 spectrometers forming a circular equiangular array in the plane normal to the X‐ray propagation and four spectrometers at 54.7° angle relative to the principle linear X‐ray polarization axis with orientations in the forward and backward direction of the light propagation. The spectrometers are capable of independent and minimally chromatic electrostatic lensing and retardation, in order to enable simultaneous angle‐resolved photo‐ and Auger–Meitner electron spectroscopy with high energy resolution. They are designed to ensure an energy resolution of 0.25 eV across an energy window of up to 75 eV, which can be individually centered via the adjustable retardation to cover the full range of electron kinetic energies relevant to soft X‐ray methods, 0–2 keV. The full spectrometer array will enable non‐invasive and online spectral‐polarimetry measurements, polarization‐sensitive attoclock spectroscopy for characterizing the full time–energy structure of SASE or seeded LCLS II pulses, and support emerging trends in molecular‐frame spectroscopy measurements.